Artocarpus hirsutus Lam Leaf Extract-Evaluation of Analgesic and Anti-Inflammatory Activity - M. Karthik; Ullas Prakash D’Souza; Prasanna Shama Khandige; Vandana Sadananda; S. Gowrish; Savadamoorthi Kamatchi Subramani (Advances in Pharmacological and Pharmaceutical Sciences)
The study involved extraction, identification, and evaluation of pharmacological activities of the phytochemicals present. Artocarpus hirsutus Lam, commonly known as Wild jack is a greatly valued medicinal plant, which belongs to the plant family Moraceae. Preliminary phytochemical screening studies indicated the presence of flavonoids, saponins, tannins, glycosides, and alkaloids. This study estimated the analgesic and anti-inflammatory prospective of ethanolic leaf extract of Artocarpus hirsutus Lam. The findings showed that at various doses of 100, 200, and 400 mg/kg body weight when administered orally to rats, analgesic effects were produced, also the anti-inflammatory effect studied by carrageenan-induced rat paw edema test showed major anti-inflammatory action. The result indicates that the leaf extract of Artocarpus hirsutus Lam possesses major analgesic and anti-inflammatory activity and therefore requires further investigations to better understand the mechanism of action.